The Influence of Fashion Involvement, Hedonic Consumption, and Shopping Lifestyle on Generation Z Consumer Preferences Through Hedonic Shopping Motivation (A Study on Inzia Scarf Hijab Resellers in Kediri) - Nadhiva Auliya Fatmala; Nurul Azizah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of Fashion Involvement, Hedonic Consumption and Shopping Lifestyle on the preferences of Generation Z consumers, with Hedonic Shopping Motivation as an intervening variable. The focus of this research is on Inzia Scarf resellers in Kediri City. This type of research is associative, employing a quantitative approach and using closed-ended questionnaires as the data collection technique. The respondents involved are 150 Generation Z consumers/resellers who actively shop for Inzia Scarf. Based on data analysis techniques including validity tests, reliability tests, bootstrapping tests, goodness-of-fit tests and hypothesis testing using path analysis, the data were processed using Structural Equation Modeling (SEM) with SmartPLS (Partial Least Square). The results indicate that Fashion Involvement and Hedonic Consumption do not significantly affect Consumer Preferences, while Shopping Lifestyle and Hedonic Shopping Motivation have a significant impact on Consumer Preferences. Furthermore, Hedonic Shopping Motivation mediates the influence of Fashion Involvement, Hedonic Consumption, and Shopping Lifestyle on Consumer Preferences. The variable that most significantly affects Consumer Preferences is Hedonic Shopping Motivation, followed by Shopping Lifestyle, then Fashion Involvement and Hedonic Consumption. This study provides theoretical implications by enriching the understanding of consumer behavior and market segmentation, as well as practical implications for companies in enhancing marketing strategies, product development, and shopping experiences following Generation Z preferences.